(3GdbUjOI GdYbGHjI aj UfGYI GdcjejGAs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3abd ddPi dGjbHd GdfUM jGaJi Ydjc Hac GdQeR Cf QeJ JZdHG s
(3BNQgG (B:s
(3Ydjg UdGI Gddg eGdGM HGQb heGdedY GdMGOi SejQG hCWQHG BNQ GdTQM(B: (3hgPG eG GfJgi EdjfG ef TQM gPg GdbUjOI hGddg Gdehab GdgGOi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B37 - (3U(B41s
(3GdfSNI HgG MhGTs
(3jdjgG TQM GdbUjOI Ke jdjgG ahGFO hfbhd eNJdaI ai UfGYI GdcjejG hJOHjQ GdMLQ ef cdGe Pi Gdfhf hGdLfjO CadGWhf hSdGe GdCehi heMeO GdjROi hef cJGH GdaJhMGJ GdZjHjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B87 s
Keywords: (3GdcjejGA h GdWHjYjGJs